Istihsan Concept and its Application in Determining the Legal Status of Halal Tourism - Widodo, Prima Ariyo (Universitas Muhammadiyah Surakarta, 2023)
Linguistically speaking, Istihsan is the masdar version of the word Istahsan - Yastahsin - Istihsana, which denotes thinking about, pondering the existence of, or seeking for something better to follow. The definition of